Blended Education Standard Template - Brejc, Mateja; Flogie, Andrej (Razvoj standarda kombiniranega poučevanja v Sloveniji, 2025)
The authors present the key findings of a group of researchers at the CRP in the form of a proposal for a standard for blended learning in higher education, based on international guidelines and national documents. The proposed standard focuses on creating a uniform terminology, defining key areas and determining quality criteria for implementing blended learning. The standards are divided into organizational (institutional framework, infrastructure, support for teachers and students, quality) and pedagogical-didactic (program planning, course delivery, assessment). The chapter emphasizes that the standards do not prescribe a rigid method of implementation, but allow for flexibility depending on the context of the higher education institution. The key goal is to ensure comparable quality of learning regardless of the form of implementation, to promote the thoughtful use of technology and to support the systematic integration of digital tools into the pedagogical process.